THE EFFECT OF RECIPE DEMONSTRATION TECHNIQUE ON STUDENTS’ WRITING COMPETENCE IN PROCEDURAL TEXT - Valia Alviana (Journal of Languages and Language Teaching, 2019)
This study was aimed at finding the effect of recipe demonstration technique towards students' writing skill in the procedural text at the food and beverage department. It was found that the students of SMK Negeri 1 Batulayar have problems in implementation writing procedural texts, thus the researcher conducted a quasi-experimental class. This research involved 62 students at grade tenth of SMK Negeri 1 Batulayar. The purpose of this research was to find out the effect of recipe demonstration toward students’ writing skill in procedural text. In collecting the data, the researcher conducted all procedures of data collection, starting from pre-test, treatments, and ended up with post-test. The quantitative data was obtained through the result of post-test of the experimental and control class. The analysis method used was independent sample t-test to find out the effect of using recipe demonstration toward students writing skill in procedural text. While the qualitative data was obtained through observation, the researcher acts as the main instrument in identifying the selected students' worksheet through a desk study within five aspects assessed in a procedural text. In this research, the researcher used the technique of data analysis which is involving three steps:  (1) data reduction, (2) data display, and (3) conclusion drawing/verification. The researcher got the result by using SPSS analyses, and the score of t-test indicated that the Sig-2 tailed< 0.05 and the t-test shows > t-table, that is the result of the t-test is 3.562 while t-table is 1.66, and it can be concluded that the hypothesis that the researcher set is accepted. In conclusion, the implementation of recipe demonstration is effective to increase students' writing competence in the procedural text of students' at F & b department SMK Negeri 1 Batulayar.